Pergulatan Islam dan Adat: Studi Kualitatif Pada Masyarakat Kampung Urug - Sumantri, Irman (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
The review of Islam and adat is a dialogue about the encounter between religion and mores. In this discussion, there is a relationship that is in line between them. This research attempts to examine the dialog between Islam and mores in the community in Kampug Urug, Bogor Regency. The approach used in this study is a qualitative research. In this study, the results indicate a strong synergy between the strength of heart in carrying out activities as well as procedures and obedience in religion. The existence of this synergy serves to unite the two of them in carrying out life. Islam is applied in life and still permanently maintains the prevailing customs, then it is transformed into the meaning of faith and tawhid. Thus, the dialog between Islam and mores of the community of Kampung Urug shows that there is a tendency that rises a new culture with local nuances. This does not mean that Islam is not preserved its purity, but is implemented in local wisdom. Even though they accept Islamic teachings as a belief, they do not eliminate their local ancestral traditions and accept modern currents.